Evaluation of hydrogen bonds formation in the selected rare sugars based on 6-31G*and 6-311++ G(d,p) basis sets - Kotena, Zahrabatoul Mosapour (Springer, 2021)
Rare sugars are monosaccharides with tremendous potential for applications in pharmaceutical, cosmetics, nutraceutical, and flavors industries. The four rare sugars, including gulose, allose, altrose, and talose, are stereoisomers that are different in the hydroxyl group orientation (axial or equatorial) on the C2-4 atoms. The basis sets effect in evaluation of the possibility intramolecular hydrogen bonding (H-bonds) in the selected rare sugars was studied from 6-31G* to 6-311 ++ G(d,p) basis sets using DFT, AIM, and NBO methods. The results show that the selected rare sugars are more stable at 6-311 ++ G(d,p) basis sets compared to 6-31G* because their electronic energies were reduced between 158 and 164 (kcal.mol(-1)). The overall effect of basis set enhancement is to decrease H-bond energies in the range of 1.25 to 2.51 (kcal.mol(-1)) and stabilization energies between 2 and 5 (kcal.mol(-1)) in the selected rare sugars at the DFT level of theory. The intramolecular H-bond distances, H-bond energies obtained from the AIM analysis, and also the second-order stabilization energies obtained from the NBO analysis were fluctuated largely depending on the basis set. In summary, it was found that the use of 6-311 ++ G(d,p) basis set to be more efficient results in rare sugars geometry than the 6-31G* basis set.